Making Video Documentation of SIM Innovation for Empowerment of Regional Development Planning Agency for Iga Award Preparation - Wiji Nurastuti; Netci Hesvindrati; Kumara Ari Yuana; R. Hennry Poerwanto B (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Empowerment Information System Management is a management information system that contains data on the population of the city of Yogyakarta, the poor, and data on interventions that have been carried out by the Regional Government to the population. Yogyakarta city population data is based on Net Consolidated Data issued by the Ministry of Home Affairs every 1 semester. The data on the poor population are the Integrated Social Welfare Data from the Ministry of Social Affairs and the Social Protection Security Target Family data set by the Mayor of Yogyakarta. Intervention data are all intervention activities carried out by the Regional Government that target the population directly, both physical and non-physical, such as training, repairing Uninhabitable Houses, improving sanitation, and providing social assistance for persons with disabilities and neglected elderly people, etc. The implementation of this program is regulated in Yogyakarta Mayor Regulation Number 50 of 2019 concerning Single Data Management for Electronic-Based Intervention Targets. In practice, the Regional Government who will intervene proposes the Citizen's ID of the population to be intervened through the Empowerment Information System Management, then from Bappeda will give approval or reject the Regional Government's proposal. If one of the Citizen's ID is proposed for the same activity, the system will automatically block it or it cannot be proposed. If it has been approved, the activity can be carried out and then the date of implementation is also entered into the Empowerment Information System Management, This proposal was prepared in the context of the Development and Empowerment of Yogyakarta City Resources; and to realize the Independent Learning Program for the Independent Campus in the City of Yogyakarta and follow up on the Letter of the Head of the Yogyakarta City Bappeda Number 074 / 345 dated June 7, 2021 regarding the Application for Assistance, hereby request assistance to assign Mrs. Wiji Nurastuti, MT and the team in the framework of cooperation assistance in making a video documentation of Information System Management innovation for the Empowerment of the Yogyakarta City Regional Development Planning Agency.